2012
DOI: 10.1158/0008-5472.sabcs12-pd07-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD07-05: A randomized controlled trial comparing zoledronic acid plus chemotherapy with chemotherapy alone as a neoadjuvant treatment in patients with HER2-negative primary breast cancer

Abstract: Background: Zoledronic acid (ZOL) is a nitrogen-containing bisphosphonate, and it induces osteoclast apoptosis and inhibits bone resorption by inhibiting the mevalonate pathway. ZOL has also been found to have antitumor effects that include an angiogenesis inhibiting action, an inhibitory effect on tumor cell adhesion to bone, an inhibitory effect on invasion of the extracellular matrix, and activation of a gdT cells. In addition, it has been found to have a synergistic anti-proliferative effect when used in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study investigators provided an information form -that was approved by the institutional review board -to all patients before enrollment to explain the trial and obtain voluntary written informed consent to participate in the study. The study was registered at the University Hospital Medical Information Network as UMIN000003261 (13).…”
Section: Methodsmentioning
confidence: 99%
“…The study investigators provided an information form -that was approved by the institutional review board -to all patients before enrollment to explain the trial and obtain voluntary written informed consent to participate in the study. The study was registered at the University Hospital Medical Information Network as UMIN000003261 (13).…”
Section: Methodsmentioning
confidence: 99%
“…The pCR rate was higher in the bisphosphonate group than in the non-bisphosponate group, although not statistically significant (25.4% vs. 16%, p = 0.11). Furthermore, the JONIE-1 group recently presented data of their phase III trial comparing neoadjuvant chemotherapy with and without zoledronic acid [ 43 , 44 ]. Interestingly these results not only suggested that postmenopausal women benefit more from zoledronic acid therapy (18.4% vs. 5.1%, p = 0.07), but also that triple-negative bisphosphonate-treated patients respond better than their chemotherapy-only counterpart (35.3% vs. 11.8%, p = 0.06).…”
Section: The Future Of Bisphosphonates and Neoadjuvant Therapymentioning
confidence: 99%